Africa and the World
XXXV, 520 p. 19 illus., 17 illus. in color.
Keywords: This book probes key issues pertaining to Africa’s relations with global actors. It provides a comprehensive trajectory of Africa’s relations with key bilateral and major multilateral actors, assessing how the Cold War affected the African state systems’ political policies, its economies, and its security. Taken together, the essays in this volume provide a collective understanding of Africa’s drive to improve the capacity of its state of global affairs, and assess whether it is in fact able to do so. Dawn Nagar is Senior Researcher at the Centre for Conflict Resolution (CCR), Cape Town, South Africa. Charles Mutasa is an independent development policy consultant. He served as Deputy Presiding Officer of the first African Union-Civil Society Organisations (CSO) Bureau, and as vice-president of the African Union Economic Social and Cultural Council (ECOSOCC) between 2005 and 2008. He was the former Executive Director of the African Forum and Network on Debt and Development (AFRODAD). .